Extreme Floods and Droughts under Future Climate Scenarios - Markus, Momcilo; Cai, Ximing; Sriver, Ryan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Hydroclimatic extremes, such as floods and droughts, affect aspects of our lives and the environment including energy, hydropower, agriculture, transportation, urban life, and human health and safety. Climate studies indicate that the risk of increased flooding and/or more severe droughts will be higher in the future than today, causing increased fatalities, environmental degradation, and economic losses. Using a suite of innovative approaches this book quantifies the changes in projected hydroclimatic extremes and illustrates their impacts in several locations in North America, Asia, and Europe.